The competence of an arbitral tribunal under the Convention on the Settlement of Investment Disputes between States and Nationals of other States : an analysis of bilateral investment treaties provisions and a question of admissibility - Rey de Castro Alarco, Álvaro Santiago (Agenda Internacional, 2007)
El artículo no presenta resumen.